Shifts in Innovation Focus in Response to Online and Offline Shareholder Activism: Unpacking Patterns in Family and Non-Family Firms - Wu, Bao; Zhang, Yuxin; Fang, Hanqing “Chevy” (Entrepreneurship Theory and Practice, 2026)
This study investigates how online and offline shareholder activism influences a firm’s innovation focus—on exploration or exploitation—in family and non-family firms. We theorize, from a mixed gamble perspective, that such activisms pose distinctive threats to a firm’s economic and non-economic interests. We analyze 7,887 firm-year observations from Chinese listed firms (2012–2022) and find that non-family firms are more likely than family firms to shift toward exploitation in response to offline activism, and family firms are more inclined to focus on exploration when facing online activism. Additionally, second-generation family firms are found to be more responsive than first-generation firms to both forms of shareholder activism.